The effect of heat on tissue extensibility: A comparison of deep and superficial heating - Robertson, Val J.; Ward, Alex R.; Jung, Peter (Archives of physical medicine and rehabilitation, 2005)
Robertson VJ, Ward AR, Jung P. The effect of heat on tissue extensibility: a comparison of deep and superficial heating. Arch Phys Med Rehabil 2005;86:819–25. To compare the effects of deep heating (shortwave diathermy [SWD]) and superficial heating (hydrocollator packs) on tissue extensibility. A double-blind, repeated-measures study. Possible effects of sex and intervention order were controlled. A clinical laboratory. Twenty-four subjects with no neurologic or musculoskeletal pathologies affecting their lower limbs. Three intervention conditions: deep heating (SWD), superficial heating (hot packs), and no heating were applied in preallocated order to each subject at least 36 hours apart. Ankle dorsiflexion in weight bearing was measured by using an inclinometer to ascertain changes in the extensibility of the calf muscles and associated soft tissues. Deep heating increased the range of ankle dorsiflexion by 1.8°±1.9°. The change in ankle dorsiflexion after superficial and no heating was 0.7°±1.5° and −0.1°±1.0°, respectively. Deep heating, in the absence of stretching, increases tissue extensibility more than superficial heating or no heating. Superficial heating is more effective than no heating, but the difference was not statistically significant.